2018
DOI: 10.3892/ijmm.2018.3386
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of HIV-1 host factor COMMD1 by the Sp family

Abstract: Copper metabolism Murr1 domain containing 1 (COMMD1) has multiple functions in the regulation of protein stability at the plasma membrane and in the cytoplasm. However, the regulation of COMMD1 transcriptional has remained to be elucidated. In the present study, the 5'‑flanking region (‑1,192/+83 bp) of the human COMMD1 gene was cloned. It was observed that the COMMD1 promoter region contains GC‑rich region that has 7 putative Sp1‑binding sites via in silico analysis. The proximal promoter region at ‑289/+83 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Besides hCtr1, Sp1 is also known to regulate ATP7A through promoter binding [97]. Moreover, Sp1 also transcriptionally regulates COMMD1 by binding to its promoter [98]. Although cDDP does not directly act upon Sp1, or very weakly at best, it was found that cDDP enhances Sp1-DNA binding in vitro [94], consistent with the previous observations that cDDP induces Sp1 and hCtr1 expression [99].…”
Section: The Cu-sp1-hctr1 Inter-regulatory Loop In Humanssupporting
confidence: 87%
“…Besides hCtr1, Sp1 is also known to regulate ATP7A through promoter binding [97]. Moreover, Sp1 also transcriptionally regulates COMMD1 by binding to its promoter [98]. Although cDDP does not directly act upon Sp1, or very weakly at best, it was found that cDDP enhances Sp1-DNA binding in vitro [94], consistent with the previous observations that cDDP induces Sp1 and hCtr1 expression [99].…”
Section: The Cu-sp1-hctr1 Inter-regulatory Loop In Humanssupporting
confidence: 87%
“…This review focuses on the biological roles of the COMMD protein family and the particularity of COMMD1, and involves as far as possible the research results about other members of the COMMD protein family. Given the functional diversity of COMMD proteins, the COMMD protein family is implicated in numerous disease processes, such as hepatitis ( 8 , 9 ), myocardial ischemia ( 10 12 ), cerebral ischemia ( 13 ), HIV infection ( 14 , 15 ), and malignancies ( 4 ). COMMD1 deficiency induces or worsens hepatitis in mouse and dogs, and the mechanism might involve an increase in intracellular hepatic copper and hepatic lipid accumulation ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Host proteins are similarly recruited to viral promoter regions for the analogous replicative processes. For example, HIV-1 recruits Sp1 to its COMMD1 (COMM domain-containing protein 1) promoter region to regulate transcription [ 21 ]; and in human papillomavirus (HPV), Sp1, AP1, and NF1 are recruited to early promoters to initiate transcription [ 22 , 23 , 24 ]. Thus, for effective infection, those regions that interact with the host proteins would also need to be highly conserved.…”
Section: Introductionmentioning
confidence: 99%